1996
DOI: 10.1063/1.871996
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar magnetic fluctuation-induced heat transport in toroidal devices

Abstract: The total magnetic fluctuation-induced electron thermal flux has been determined in the Madison Symmetric Torus ͑MST͒ reversed-field pinch ͓Fusion Technol. 19, 131 ͑1991͔͒ from the measured correlation of the heat flux along perturbed fields with the radial component of the perturbed field. In the edge region the total flux is convective and intrinsically ambipolar constrained, as evidenced by the magnitude of the thermal diffusivity, which is well approximated by the product of ion thermal velocity and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…We extend here the prior calculations of ambipolar constraints in magnetic fluctuation-induced transport [14][15][16] to calculate the heating of ions intrinsic to these constraints. Although the origin of these constraints and the underlying physics that introduces them has been detailed in the literature, 13,[18][19][20][21][22] we present here a brief introduction.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…We extend here the prior calculations of ambipolar constraints in magnetic fluctuation-induced transport [14][15][16] to calculate the heating of ions intrinsic to these constraints. Although the origin of these constraints and the underlying physics that introduces them has been detailed in the literature, 13,[18][19][20][21][22] we present here a brief introduction.…”
Section: Introductionmentioning
confidence: 96%
“…13 The role of turbulent granularity in magnetic fluctuation-induced electron transport has been documented in a series of papers examining successively higher transport moments. [14][15][16] For the particle and field-aligned momentum fluxes, it was found that the transport from mag-netic turbulence nearly vanishes relative to the electrostatic fluxes and the flux of the non self-consistent quasilinear approximation. 14,15 The residual transport is smaller than the quasilinear or electrostatic fluxes by the ratio of ion to electron current contributions in Ampére's Law, and therefore resembles an ambipolar-constrained transport flux.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations